Eu:Y2O3 highly dispersed fluorescent PVA film as turn off luminescent probe for enzyme free detection of H2O2 - Kumar D.; Umrao S.; Mishra H.; Srivastava R.R.; Srivastava M.; Srivastava A.; Srivastava S.K. (My University, 2025)
In this work, a novel sensing scaffold consisting highly dispersed Eu:Y2O3 fluorescent flexible film of poly vinyl alcohol (EYCP) was synthesized by simple mixing method and applied to facilitate non-enzymatic detection of hydrogen peroxide (H2O2) by turn off probe of fluorescence. The fluorescence spectra of EYCP consisting number of emission sharp transitions from excited, 5D0→7Fj (j = 0, 1, 2, 3, 4) energy levels of doped Eu3+ ion in Y2O3 host. In the presence of H2O2, the fluorescence intensity of the EYCP film was quenched due to the reduction of electron–hole pair recombination in Eu centers by electron transfer from Eu–O excited state to H2O2 energy level rather than 5D0 state of Eu3+, which reduces the number of electron in 5D0 state. The EYCP film shows excellent fluorescence quenching in presence of H2O2 by significantly increasing concentration of H2O2 and completely quenched at ∼150 μM. A linear relationship is observed between 0.0 and 60 μM with a correlation coefficient of 0.989. H2O2 sensing is also compared with the EYC nanoparticles. This study is expected to have a significant impact on further study of the Eu:Y2O3 fluorescent flexible film for wide range applications. © 2017 Elsevier B.V.